Bad sex : truth, pleasure, and an unfinished revolution - Aronowitz, Nona Willis, 1984- (Plume, 2022)
"From Teen Vogue sex and love columnist Nona Willis Aronowitz, a blend of memoir, social history, and cultural criticism that probes the true meaning of desire and sexual freedom in today's age. At thirty-two years old, everything in Nona's life, and in America, was in extreme disarray. Her marriage was falling apart. Her nuclear family was slipping away. Her heart and libido were suffering from overexposure. Embroiled in an era of fear, reckoning, and reimagining, her assumptions of what "sexual liberation" meant were suddenly up for debate. It was in that moment of personal and political sea change that Nona turned to the words of history's sexual revolutionaries-including the writing of her late mother, early radical pro-sex feminist Ellen Willis. At a time when sex has never been more accepted and feminism has never been more mainstream, Nona asked herself: What, exactly, do I want? And are my sexual and romantic desires even possible amid the horrors and bribes of patriarchy, capitalism, and white supremacy? Bad Sex places Nona's intimate history alongside her family history and other stories stretching back nearly two hundred years: those of ambivalent wives and unchill sluts, Free Lovers and radical lesbians, sensitive men and woke misogynists, women who risk everything for sex, who buy sex, reject sex, have bad sex and good sex. The result is a brave, bold, and vulnerable exploration of the enduring barriers to sexual freedom. This book lays bare the triumphs and flaws of contemporary feminism and also helps shine a light on universal questions of desire"--